From a cell model to a fish trial: Immunomodulatory effects of heat-killed Lactiplantibacillus plantarum as a functional ingredient in aquafeeds for salmonids - Rocha, Sérgio Domingos Cardoso; Lei, Peng; Morales-Lange, Byron; Mydland, Liv Torunn; Øverland, Margareth (Frontiers in Immunology, 2023)
Paraprobiotics (dead/inactivated probiotics) are promising candidates in functional feeds to promote growth performance, modulate intestinal microbiota and enhance immune response of fish. During industrial production, fish are exposed to several stressful conditions such as handling, sub-optimal nutrition and diseases that can lead to reduced growth, increased mortalities and large economical losses. Such problems can be mitigated by use of functional feeds, leading to more-sustainable aquaculture and improved animal welfare. Lactiplantibacillus plantarum strain L-137 is a common bacterium found in fermented Southeast Asian dish made from fish and rice. The benefits of its heat-killed form (HK L-137) related to growth performance and immunomodulation have been studied in farmed fish such as Nile Tilapia (Oreochromis niloticus), striped catfish (Pangasianodon hypophthalmus) and bighead catfish (Clarias macrocephalus). To study if such benefits can also be observed in salmonids, we worked both at in vitro level using an intestinal epithelium cell line from rainbow trout (Oncorhynchus mykiss; RTgutGC) stimulated with HK L-137 (Feed LP20™) and at in vivo level with pre-smolt Atlantic salmon (Salmo salar) fed HK L-137 at different inclusion levels (20, 100 and 500 mg of Feed LP20™ kg-1 feed). In RTgutGC, the results showed that the barrier function of the cell monolayer was strengthened along with an increased production of IL-1β and a decreased production of Anxa1, indicating a modulation of the immune response. Interestingly, a similar trend was detected at the in vivo level in distal intestine from fish fed the highest inclusion level of HK L-137. Here, a lower production of Anxa1 was also detected (after a 61-day feeding period) in addition to an increase of total plasma IgM in the same group. Furthermore, the RNA-seq analysis showed that HK L-137 was able to modulate the gene expression of pathways related to molecular function, biological process and cellular component in distal intestine, without compromising fish performance and gut microbiota. Taken together, our study has shown that HK L-137 can modulate physiological response of Atlantic salmon, making fish more robust against stressful conditions during production.